The Analysis of Asymptotic Rate-Distortion of Symmetric Remote Gaussian Source Coding: A Comparison of Centralized Encoding and Distributed Encoding - wang, Mengzhen Jr (My University, 2019)
Take into account a symmetric multivariate Gaussian source with ` components, which are corrupted by independent and identically distributed Gaussian noises; these noisy components are compressed at a certain rate, and the compressed version is leveraged to reconstruct the source subject to a mean squared error distortion constraint. We analyze rate-distortion performance for both centralized encoding (where the noisy source components are jointly compressed) and distributed encoding (where the noisy source components are separately compressed). Among other things, it is indicated that the gap between the rate-distortion functions associated with these two scenarios admits a simple characterization in the high dimension.